If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-1=5x+12
We move all terms to the left:
3x-1-(5x+12)=0
We get rid of parentheses
3x-5x-12-1=0
We add all the numbers together, and all the variables
-2x-13=0
We move all terms containing x to the left, all other terms to the right
-2x=13
x=13/-2
x=-6+1/2
| 6x+3=13x-2 | | 0.20(y-8)+0.06y=0.16y-1.4 | | 14x-5=51 | | 8=8(c-87) | | 15=7+4c | | 3a(4a-5)+7=3 | | 82-x=(1/4)2x | | -8=n/4-10 | | 2(x–2/3)=0 | | -8=n4-10 | | 1/2x-19=11x= | | x/4+13=21 | | (6x+7)(5x^2+4x=7) | | 44=-3b-1 | | -15=-12x+21 | | (-6w-1)(-5w-8)=0 | | 54.4=n-3 | | 9x+15=2x+20+2x | | 2a-6=30a= | | y=-2/3(0)+10=10 | | Y=11x+400 | | 8x-14=180+2x+10=180 | | 8x-14+2x+10=180 | | x/2+3=x+4 | | (3-6x)/3=7x-2 | | -6/7v=42 | | 3y–12=3 | | 7x–3=6x–13 | | t−6t+10=−5−3t | | 4f+7=4f+5 | | 6.1=32x-2.9x+2.5 | | 0.05x+0.03(35000–x)=1250 |